THE ASSOCIATION OF SERUM VITAMIN D AND SUPEROXIDE DISMUTASE LEVEL IN WOMEN WITH POLYCYSTIC OVARY SYNDROME - Muhammad, Muhammad Abd al-Qahar; Zughair, Nada Khaled; Mahdi, Ruqayyah Khalil; Mohsen, Amna Farouk; Blais, Roaa Qasim; Blais, Russul Qasim (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: This study aimed at investigating the association of serum vitamin D and superoxide dismutase level in women with polycystic ovary syndrome (PCOS) as well as non-PCOS healthy ovulatory women. Methods: A total of 20 patients with polycystic ovaries and 20 of their age matched healthy control participates was included in this study. The patient samples were collected from women who reproductive age between 18 and 40 with PCOS. Results: The results of the current study showed a high level of SOD enzyme concentration versus decrease in the level of vitamin D in the PCOS patients compared to the healthy group. Conclusion: There is an opposite effect of superoxide dismutase level and vitamin D on polycystic ovary syndrome (PCOS).